MODEL KONSEP TEORI KEPERAWATAN HILDEGARD ELIZABETH PEPLAU DENGAN SKIZOFRENIA - Istinganah; Irna Nursanti (Yayasan Nusantara Hasana Berdikari, 2024)
This paper aims to describe the application of Hildegard Elizabeth Peplau's nursing theory concept model in caring for individuals with schizophrenia. This theory emphasizes the interpersonal relationship between nurses and patients as a key factor in the healing process. In the context of schizophrenia, this relationship becomes more complex due to the characteristics of the symptoms and communication challenges. Nurses serve as